El modelo integrador en la educación infantil en los niños de inicial 2 paralelo “a” de la unidad educativa Fernando Daquilema de la parroquia veloz cantón Riobamba provincia de Chimborazo periodo 2017-2018 - Paguay Caranqui, Edith Margarita (2018)
The objective of this research was to determine the importance of the integrating model in early childhood education for children. Initial 2 Parallel "A" of the Fernando Daquilema Educational Unit of the Parroquia Veloz Cantón Riobamba Province of Chimborazo Period 2017-2018. " Because it is of great relevance within the educational context, this is how the integrative model is productive educational change are full of contradictions that are often not considered compatible, child education, the contents must take into account the flexible structures that allow them interact and generate actions that lead to personal development and school abilities of children, the methodology used was a non-experimental design, by the descriptive level, by the field and bibliographical site, the population was the students of the Unit Educational "Fernando Daquilema", the sample was non-probabilistic and intentional of 22 children from Initial 2, the technique was the Observation and the Instrument the observation card which helped us to interpret the data to be able to reach the conclusion that it has been possible to conclude that the integrative model has several advantages that facilitate the development of the children's education of the students, it is as well as the relation that must be generated between teacher and students, the feasibility for the intervention of a quality education, the creation of new strategies to improve the learning of the children are some of the many advantages what it brings.